Synthesis of Glycerol Monooleate with MgO-Impregnated Natural Zeolite Catalyst - Mukti, Nur Indah Fajar; Putri, Avicenna Mustika; Nur, Wahidah; Arobi, Ibnu; Arifa, Muhammad Ridho (Sainteknol : Jurnal Sains dan Teknologi, 2024)
Glycerol Monooleate (GMO) is synthesized via esterification, which involves the reaction between glycerol and oleic acid to yield monoglyceride esters. The esterification reaction is intrinsically slow, requiring the use of a catalyst to decrease the activation energy. The catalyst used in this study is a naturally occurring zeolite catalyst that has been altered through acid treatment and impregnation with Mg(NO3)2, and then subjected to calcination to convert it into MgO. Typically, this research consists of two steps: an initial phase where a natural zeolite catalyst is altered, followed by a subsequent phase where glycerol monooleate production. This study investigates the effects of different variables on the reaction. The variables include temperature (140–180oC), catalyst loading (3-10 %weight), glycerol to oleic acid ratio (2:1, 3:1, 4:1), reaction time (0–180 minutes), and stirring speed (125-525 rpm). The research results demonstrate that the highest conversion rate was achieved with a temperature of 180oC, a catalyst concentration of 10%, and a reactant ratio of 3:1 (glycerol to oleic acid). The ideal response time was found to be 120 minutes. The reaction kinetics can be estimated by employing a pseudo reaction equation that follows a first-order rate law. The rate constant, represented by k', can be approximated using the Arrhenius equation. The reaction has an activation energy of -18.64 kJ.mol-1, and the value of A is 1.41 cm3.g-1.minute-1.